VERIFICATION OF ECONOMIC-MATHEMATICAL MODEL OF INNOVATIVE DEVELOPMENT OF COMMUNICATION AND INFOTELEKOMMUNIKATION OF RUSSIA - Armen Sh. Galstyan; Anastasiya A. Shiyanova; Vladimir F. Minakov; Tatyana E. Minakova (Вестник Северо-Кавказского федерального университета)
In article the current state and dynamics of development of infotelekommunikation and communication of Russia is analyzed. Innovative character of factors of development of branch of communication and telecommunications is noted. Innovative signs are found both in technological base of branch, and in products of the enterprises of information and telecommunication sector. Adequacy of models of diffusive development of branch locates. Two components of increase in demand for information and telecommunication services are allocated. Nature of their influence on dynamics of demand is defined. The Bass model for the description of dynamics of the income of branch of communication and telecommunications is verified. For identification of parameters of the verified model temporary ranks of dynamics of the income are used. The model allows to define trends of dynamics of the income of branch of telecommunications, and also to operate them for acceleration of positive dynamics.